URGENSI KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGELOLAAN KINERJA GURU - Muttaqin, Muhammad Fahrul; Rindaningsih, Ida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the principal’s leadership in managing teacher human resources at SD Muhammadiyah 1 Gempol. This research employed a qualitative descriptive approach involving the principal, teachers, and educational staff as research subjects. Data were collected through interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The results of the study indicate that the principal plays not only an administrative role but also functions as a leader, mentor, and motivator in managing teacher performance. Leadership strategies are implemented through continuous teacher development programs, academic supervision, and effective communication. The principal’s leadership has a positive impact on improving teachers’ motivation, discipline, and instructional quality, although several challenges are still encountered in its implementation. This study contributes to the development of Islamic Educational Management studies, particularly in the field of school leadership and teacher human resource management within the context of Muhammadiyah elementary schools. Keywords: Principal Leadership, Human Resources, Teacher Performance